Consumer Profile Analysis for Marketplace Application Design at Unggascare Startup - Raden Muhamad Raihan Fathurahman; Kristina Sisilia; Agus Maolana Hidayat (Indonesian Journal of Entrepreneurship and Startups, 2024)
This research aims to identify consumer profiles and develop a strategy for developing the Unggascare startup application based on analysis of interviews with three informants from the poultry product buyer segment at Sukahaji Market. The analysis results show that consumers want quality poultry products at affordable prices, as well as improved service in terms of ease of finding products, seller responsiveness, timely delivery and affordable shipping costs. The majority of informants use smartphones and the internet to search for product information, including through marketplace platforms and social media such as Facebook. The implication of these findings is that there is an opportunity for Poultrycare to design an application that meets consumer needs in finding and purchasing poultry products more easily, as well as strengthening consumer loyalty through a satisfying experien ce.